Transilluminated powered phlebectomy in the treatment of large area venous leg ulcers: A case‐control study with 3 years follow‐up. (30th January 2019) - Chen, Siyu; Zeng, Qiu; Fu, Qining; Li, Fenghe; Zhang, Mao; Zhao, Yu
Abstract: Objective: To evaluate the efficacy, safety and long‐term outcome of TIPP for the adjunct therapy of superficial venous reflux‐related VLUs. Methods: A total of 93 consecutive patients (104 legs) with superficial venous insufficiency‐related VLUs who underwent TIPP (53 legs) or conventional phlebectomy (51 legs) between January 2010 and December 2013 were retrospectively studied. Results: Compared to patients in the conventional phlebectomy group, TIPP patients had larger ulcer areas before surgery ( P  < 0.005). However, TIPP group required a significantly shorter operation time ( P  < 0.005), fewer incisions ( P  < 0.005) but less ulcer healing time (1.25 month vs 2.5 months, P  < 0.05). No significant difference in in‐hospital and follow‐up complications was found between the two groups. For long‐term outcome, TIPP group leaded a lower ulcer recurrence rate at 36 months (13.2% vs 29.4%, P  < 0.05). Conclusion: TIPP may be an adjunct surgical method contributes to healing of VLUs, especially for large ulcer areas.